1985
DOI: 10.1007/bf00501209
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the neuromuscular blocking drugs alcuronium, decamethonium, gallamine, pancuronium, ritebronium, tercuronium and d-tubocurarine with muscarinic acetylcholine receptors in the heart and ileum

Abstract: Neuromuscular blocking drugs have a high affinity for muscarinic acetylcholine receptors in the heart atria and ileal smooth muscle. In experiments on homogenates, alcuronium, gallamine, pancuronium, tercuronium and ritebronium inhibited the binding of the muscarinic antagonist (3H)quinuclidinyl benzilate (QNB) to rat heart atria with IC50 values of 0.15-0.53 mumol X 1(-1) and to ileal longitudinal muscles with IC50 values of 0.12-0.45 mumol X 1(-1). d-Tubocurarine and decamethonium inhibited (3H)QNB binding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…We have found earlier that the neuromuscular blocker, alcuronium interacts allosterically with muscarinic receptors (Nedoma et al, 1985; and increases the specific binding of [3H]-NMS in rat heart, smooth muscle and cerebellum, but not in cerebral cortex and salivary gland (Tucek et al, 1990). This variation in the effect of alcuronium with tissue location is consistent with the distribution of M2 receptors and suggests that the drug's positive allosteric action is selective for the M2 receptor subtype.…”
Section: Effect Of Alcuronium On the Dissociation Of [3h]-nmsmentioning
confidence: 98%
“…We have found earlier that the neuromuscular blocker, alcuronium interacts allosterically with muscarinic receptors (Nedoma et al, 1985; and increases the specific binding of [3H]-NMS in rat heart, smooth muscle and cerebellum, but not in cerebral cortex and salivary gland (Tucek et al, 1990). This variation in the effect of alcuronium with tissue location is consistent with the distribution of M2 receptors and suggests that the drug's positive allosteric action is selective for the M2 receptor subtype.…”
Section: Effect Of Alcuronium On the Dissociation Of [3h]-nmsmentioning
confidence: 98%
“…The concentrations of gallamine and pancuronium used in these experiments were selected to inhibit cardiac-like (M2) receptors but have minimal actions on corticallike (M,) receptors (Dalton & Tyers, 1982;Stockton et al, 1983;Nedoma et al, 1985).…”
Section: Muscarinic Antagonistsmentioning
confidence: 99%
“…Under current-clamp, this action would be manifest as a slow membrane depolarization and increase in cell input resistance. The muscarinic suppression of IM was not blocked by low concentrations of pirenzepine (up to 300 nM), pre-applied for at least 20 min (Figure lA b,c), whereas gallamine (20 gM), a 'cardioselective' M2-receptor antagonist (Hammer & Giachetti, 1984;Nedoma et al, 1985), produced a clear inhibition of the action of muscarine ( Figure lAd). Higher concentrations of pirenzepine (500 nM-l M) did, however, exhibit an anti-muscarinic effect (not illustrated …”
mentioning
confidence: 97%
“…A further subclassification of the peripheral M2-receptor has also been suggested in view of the fact that certain skeletal neuromuscular blockers e.g. gallamine, show more selective anti-muscarinic effects on the heart (Nedoma et al, 1985), whereas antagonists such as 4-diphenyl-acetoxy-N-methylpiperidine (4-DAMP) show a relatively higher affinity for the ileal muscarinic receptor (Barlow et al, 1976). Recent intracellular studies on mammalian central neurones have suggested that both excitatory and inhibitory actions of cholinoceptor agonists can be mediated via M2-muscarinic receptors (Egan & North, 1985;McCormick & Prince, 1986a (Constanti & Galvan, 1983b evoked a smaller instantaneous step, followed by a decaying inward relaxation to the holding current level.…”
mentioning
confidence: 99%